Team Production benefits from a Permanent Fear of Exclusion - Anita Kopányi-Peuker; Theo Offerman; Randolph Sloof (Tinbergen Institute, 2015)
One acclaimed role of managers is to monitor workers in team production processes and discipline them through the threat of terminating them from the team (Alchian and Demsetz, 1972). We extend a standard weakest link experiment with a manager that can decide to replace some of her team members at a cost. The amount of contractual commitment (termination possibilities) and the precision of the managers monitoring information serve as treatment variables. Our results show that the fear of exclusion has a profound effect on team performance even if workers are imperfectly monitored; the most flexible contract induces the highest output while the one with no firing possibilities leads to the lowest production. However, once the fear is eliminated for some workers, because permanent workers cannot be fired after a probation phase, effort levels steadily decrease.
Keywords: C72; C92; M51; M55; 330; team-production; weakest-link game; exclusion; probation; experiment